Evaluation of Alternative Traffic Engineering Management with the Use of Microscopic Simulation Software Vissim - Setyadi Gunawan; Yogi Oktopianto; Tri Susila Hidayati (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
The population of Makassar City has grown by 30,965 people in the last year and represents an annual change of 1.89% from 2022. Road growth in Makassar City has only experienced growth of 0.8% - 2% per year, while vehicle growth has reached 15% - 16% per year. Congestion at unsignalized intersections of the A.P Pettarani which is the Central Business District area of Makassar City which has activities ranging from offices, economy and education. The study aims to analyze the performance and existing at the unsignalized intersection A.P Pettarani - Sultan Alauddin Makassar City as well as traffic engineering management with queue length and delay due to u-turn using VISSIM Software. The results of the existing show the current performance with a traffic delay of 30.4 seconds, a queue length of 225 meters with LOS D and traffic conflicts that crossing of 1749 and lane changes of 6264. After the alternative is implemented, the delay and queue time at the A.P Pettarani - Sultan Alauddin Intersection are significantly reduced. The delay time when the existing conditions are at 30.4 seconds drops to 16.61 seconds, the delay time at the intersection drops by 13.79 seconds or 45.36%. As well as a decrease in queue length in the existing condition of 225 m to 151 m with a decrease of 74 meters or 32.89%.